PENGANEKARAGAMAN KONSUMSI PANGAN RUMAH TANGGA MASYARAKAT PESISIR DI KOTA BENGKULU MELALUI TEKNOLOGI PENGOLAHAN PRODUK HASIL LAUT DAN NON HASIL LAUT - reswita reswita reswita; Melli Suryanty; Ellys Yuliarti (Universitas Bengkulu, 2018)
Food is an ingredient intended as food or beverage derived from biological and water resources, whether processed or unprocessed, including food additives, foodstuffs, and other materials used in the process of preparing, processing and / or making food and drink. To meet the nutritional needs of the family is very necessary for diversification of food consumption. The purposesof this community service is are 1) Providing knowledge and insight on the importance of diversification of household food consumption, 2) training on the manufacture of some processed products from seafood such as fish abon, fish rolade, and tuna meatballs, 3) Training on the manufacture of some processed products from non-marine products such as tubers combined with marine products such as tuber chips that have a taste of shrimp and sea fish can be utilized to meet family food consumption, 4) Training on the manufacture of some processed products from other non-marine products, namely processed foods from tofu and tempeh, 5) Training on packaging techniques and product labeling so that this product can be sold and can increase the fishermen's household acceptance. The targets of this technology are PKK group mothers and young women in RT IV Kelurahan Malabero. The number of trainees is 20 people. From community service activities